Optimisasi Tekanan dan Nisbah Refluks pada Pemurnian ∆-Guaiena Minyak Nilam (Pogostemon cablin) secara Distilasi Fraksional - Rahmi Rahmawati; Sarifah Nurjanah; Efri Mardawati (Institut Pertanian Bogor, 2022)
Patchouli oil is one of Indonesia's important essential oils as an export commodity. Δ-Guaiene is one of the terpenes in the oil, which is shown to have antimicrobial activity against some fungi and bacteria. Thus, the production of δ-guaiene needs to be optimized. This study aims to determine the appropriate pressure and reflux ratio for the fractional distillation process that isolates the highest δ-guaiene content. The experiment used the response surface method. The pressure of the fractional distillation process and reflux ratio were: 1;10; 20 mmHg; and 5:1; 20:1; 35:1. The temperature ranged from 270‒272°C. Various pressure did not give different yields, except at a pressure of 1 mmHg that resulted in 4% yield and δ-guaiene content of 20.46%; both conditions were optimum. The δ-guaiene was characterized for the density, refractive index, distillate formation rate, distillation time, residual mass, and electrical energy requirements, which were 0.9519, 1.5027, 4 mL/min, 1 minute, 6.31 g, and 6.0477 kW/h, respectively. The lower the reflux ratio, the faster the distillation process; the faster the processing time, the lower the energy requirement; and the higher the ratio of reflux, the purer the percentage of the δ-guaiene. The optimum process was reached as the reflux ratio was lower, where the yield and δ-guaiene content were the highest, and the processing time was faster. Keywords: δ-guaiene, fractional distillation, patchouli oil, reflux pressure, RSM